Assessment Suitability Villages of Environmental for Rural Settlement in Al Madinah Al Munawwarah Using Analytic Hierarchy Process and GIS - AL.Abdali, مليحة حامد عبدالله (Journal of King Abdulaziz University: Environmental Design Sciences, 2026)
The study aims to evaluate suitability of village environment for rural settlement in Al Madinah region according to three models of suitability: natural, human, and comprehensive. the study relied on the analytical approach based on quantitative and cartographic methods in GIS. gradual of methodology from collecting and preparing data, determining weights using hierarchical analysis method, and merging models layers according to their weights using (Calculator GIS) to produce maps to evaluate suitability of village environment for rural settlement. The results of study showed that suitability of comprehensive indicator for rural settlement ranged between 20-78%, and more than 50% of villages are concentrated in an area characterized by moderate suitability 35-40%. there is no village where suitability rate is less than 25%. the number of villages in the area characterized by suitability 25-35% is about 46 villages, 29.49% of total villages. the villages whose environmental suitability ranges 40-45% are about 24 villages,15.39% of total villages. the villages whose environmental suitability for settlement exceeds 45% four villages, 2.56% of total number. the results of relationship between distribution of villages and comprehensive suitability for settlement show a very weak inverse relationship -0.18 that is not statistically significant. the study recommends Concentration rural development plans on reversing pattern of relationship and increasing its strength, in order to ensure functional integration between villages and cities in achieving sustainable development.